Review of Eric Clarke and Nicholas Cook, eds. 2004. Empirical Musicology: Methods, Aims, Prospects. Oxford and New York: Oxford University Press - Devaney, Johanna (Current Musicology, 2005)
Empirical Musicology is a collection of articles exploring the potential for a greater integration of empirical methods into musicology and music theory. This volume is particularly timely given the increase in available personal computer power over the past ten years and the subsequent development of software that may be used to extract, analyze, and/or compile musical data. Nicholas Cook and Eric Clarke begin by asking the question, “What is empirical musicology?” and proceed to argue that in reality all musicology is empirical to some degree, in the sense that it is based in an observable reality that may be explored, explained, and generalized. The editors subsequently redefine the issue as the extent to which current musicology makes use of the methods of empirical observation, including the ways in which these observations are regulated by the discipline’s discourse and the ways in which these methods may be applied and regulated in future research. What is proposed is not so much a paradigm shift as a paradigm expansion; the empirical musicology described here applies empirical methodologies to the meaningful data already collected on a wide range of musicological topics.